Synthesis and characterization of new derivatives of CMC-g-PVA and evaluation pharmaceutical release, antibacterial activity, molecular docking - Shakere Nayyef, Rasha; hitur Awad, Sana (Journal of Neonatal Surgery, 2025)
In this research drug polymers, have been prepared by substituting drugs to polymers backbone, which raised interest as a result of the benefits systems possesses, as the first part of a continued research on conversion of carboxymethyl cellulose- (CMC) to useful biopolymer-based materials, it possesses a plethora of other noteworthy attributes like biocompatibility, renewability, nontoxicity, and biodegradability, large numbers of hydroxyl functional groups were introduced onto CMC with different drugs (sulfamethoxazole , Salbutamol phenylephrin , Sodium Fusidate , Hemayoxiline , chloramphenicol ) by grafting with polyvinyl alcohol. Evidence of prepared compound was obtained by FTIR spectra, HMR, UV visible, the CMC-g-PVA copolymer was characterized thermally by using differential scanning calorimetry and thermogravimetric analysis methods. The biological activity of the prepared pharmaceutical polymers against two types of bacteria was also studied. The molecular bonding of some of the prepared polymers was also studied. The pharmaceutical degradation of some of them was studied in different acidic and alkaline media. The controlled release for all polymers was studied in different pH=4, pH=9 values at (30-40)0C. The hydrolysis data showed that release rates are strongly dependent on the pH of the medium and temperature We concluded that the drug polymers could enhance the solubility of drug carrier polymers in water, with desirable properties, slow-release, and prolonged activity. These four methods of advanced properties and bearing of the different bioactive units, and studying Molecular Docking.